Constructive Feedback Teaching Strategy: A Multisite Study of Its Effectiveness. Issue 5 (September 2018) - Altmiller, Gerry; Deal, Belinda; Ebersole, Nancy; Flexner, Randi; Jordan, Janet; Jowell, Vicki; Norris, Tommie; Risetter, Mary Jo; Schuler, Monika; Szymanski, Kathleen; Vottero, Beth; Walker, Danielle
Abstract: AIM: The study purpose was to describe students' perceptions of feedback after participating in a teaching strategy designed to foster a view of feedback as an opportunity for improvement. BACKGROUND: Although delivering and receiving constructive feedback are essential to the role of the professional nurse, feedback has been identified as a trigger for incivility in academia and practice. METHOD: Twelve nurse educators from the Quality and Safety Education for Nurses Academic Task Force, located at nine schools of nursing across the nation, implemented a presentation about giving and receiving constructive feedback in junior and senior courses. RESULTS: Five hundred twenty-three students submitted a total of 985 posts or essays in response to viewing the presentation; seven themes were identified. CONCLUSION: Viewing this teaching strategy enabled nursing students to develop an awareness of the opportunity that constructive feedback presents for professional development, self-improvement, teamwork and collaboration, and patient safety.